Pneumonia and COVID-19 co-infection modeling with optimal control analysis - Aga, Beza Zeleke; Keno, Temesgen Duressa; Terfasa, Debela Etefa; Berhe, Hailay Weldegiorgis (Frontiers in Applied Mathematics and Statistics, 2024)
The formulation and analysis of deterministic models characterizing the dynamics of pneumonia, COVID-19, and co-infection are presented in this study. We observe that the pneumonia-only, COVID-19-only, and full co-infection models display locally asymptotically stable disease free equilibrium points when their respective R 0 are less than unity. In the models, the stability of endemic and disease-free equilibria on a global scale was taken into consideration. Additionally, the best control strategy is chosen using Pontryagin's maximal principle, and the objective function is optimized by applying control strategies like prevention and treatment. A numerical simulation was then run to validate our analytical findings.